Pengaruh Pola Asuh Orang Tua Dalam Penggunaan Gadget Terhadap Perkembangan Sosial-Emosional Kelas VI Di SDN 1 Sariwangi - Muiz, Agung Abdul; Maftuh, Ade; Zulkarnaen, Rizki Hadiwijaya (Jurnal Pendidikan Rafflesia, 2024)
The development of technology and information in the world is progressing very rapidly, which is marked by progress in the field of information and technology, and the Indonesian nation is one of the nations involved in the progress of information media and technology. Excessive use of gadgets has a bad influence on children's social-emotional development. This research aims to examine the influence of parenting patterns in the use of gadgets on the social-emotional development of class VI at Sariwangi 1 State Elementary School using qualitative research methods using descriptive analysis research, using data collection techniques, observation, interviews, questionnaires and documentation. With the research results, parents at SDN 1 Sariwangi mostly apply democratic parenting patterns and there is a positive relationship between the mother's parenting style in using gadgets and the social-emotional development of Class VI children at SDN 1 Sariwangi.